URGENSI LITERASI DIGITAL BAGI WIDYAISWARA - Ranti Nuranita; Dedi Restendi (Balai Diklat Keagamaan Jakarta, 2021)
The digital era is marked by the shift of mechanical and analog technology to digital technology. The transfer of technology has led to the disruption of human culture. One of them is in the way of thinking and acting, especially for professionals. Today, a professional must have digital literacy competence, namely the ability to access, manage, understand, integrate, communicate, evaluate, and create information safely and precisely through digital technology. Widyaiswara is a related profession. Questions arise related to this, namely,